Step 1. The equation that we have is:
![x(x+6)+4=0](https://img.qammunity.org/2023/formulas/mathematics/college/6x3tnpdfw3zapewu7khoolbchxzt0d6k0t.png)
Before we apply the quadratic formula to solve the equation, we need to simplify the expression and multiply x by (x+6):
![\begin{gathered} x(x+6)+4=0 \\ \downarrow \\ x^2+6x+4=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ntnejcaj6x7bxf5u6pap1d2jvxtk9b0e8r.png)
Step 2. The next step is to compare our equation with the general standard form of the quadratic equation:
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
And we find that the values of x, b, and c are:
![\begin{gathered} x^(2)+6x+4=0 \\ \downarrow\downarrow \\ a=1 \\ b=6 \\ c=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9p24gwyourcwzohn1h084v588dn83sq89z.png)
Step 3. We will use to values of a, b, and c in the quadratic formula:
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/jr19ixi2zltkocy82qhxfiop5lyv4hzbkm.png)
Substituting the known values:
![x=(-6\pm√(6^2-4(1)(4)))/(2(1))](https://img.qammunity.org/2023/formulas/mathematics/college/yaoror9morw9hcm4qyibq5bm35r5xbgghl.png)
Step 4. Solving the operations step by step:
![\begin{gathered} x=(-6\pm√(36-16))/(2) \\ \downarrow \\ x=(-6\pm√(20))/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5lin8wewsst74ypaunwmes1yi7aaud6g4h.png)
We can simplify the square root of 20 as follows:
![√(20)=√(4\cdot5)=2√(5)](https://img.qammunity.org/2023/formulas/mathematics/college/9gt25bi86kqh2j7gglm7y91frfcn89zl0d.png)
Therefore:
![x=(-6\pm2√(5))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/ryyyqbgph696o7c7ruytermotpr104l4cd.png)
Now we make the division by 2:
![\begin{gathered} x=(-6\pm2√(5))/(2) \\ \downarrow \\ x=-3\pm√(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g2hjxvivlcec935pms2pg44fwn4e2sdwn3.png)
Step 5. The final step is to use the + and - signs to find our two solutions:
![\begin{gathered} Solution\text{ 1:} \\ x=-3+√(5) \\ Solution\text{ 2:} \\ x=-3-√(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/52xczxg69philkwkqgyo82qth216a42rbh.png)
Answer:
![\begin{gathered} x=-3+√(5) \\ x=-3-√(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2c515au367m70rkr2h668ucnqg4bi82b38.png)